Evaluating a Drama Management Approach in an Interactive Fiction Game - Corradini, Andrea; Mehta, Manish; Ontanon, Santi (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 02, 2009)
In this paper, we evaluate a drama management approach deployed in an implementation of a graphical interactive fiction game. Our approach uses players’ feedback as a basis for guiding the personalization of the interaction. Twenty subjects, with different levels of expertise, took part in the experimental evaluation. The results indicate that our Drama Manager (DM) helps in providing a better play experience. Quantitative analysis indicates that the DM causes an average subjective improvement of 12.5% of the subjects’ play experience. Qualitative analysis from the user interview shows that all subjects noticed the difference in playing the game with and without the DM while the former way of playing was also the preferred one. The large majority of players found the hints, and ultimately the DM, helpful even if frustrating at times when these cannot be exploited directly for further proceeding in the game.